Effect of integrated nutrient management practices on growth and yield of vegetable crops grown as intercrops in coconut (Cocos nucifera) garden - KUMAR, K S NAVEEN; MAHESWARAPPA, H P; BASAVARAJU, T B (The Indian Journal of Agricultural Sciences, 2016)
Investigation was carried out at Horticulture Research and Extension Station, Arasikere, Karnataka, during kharif and summer seasons of 2012-14 to study the performance of different cropping sequences with vegetable crops and effect of integrated nutrient management practices on growth, and yield of vegetable crops under coconut (Cocos nucifera L.) based cropping system (CBCS). The experiment consisting of three cropping sequences of vegetable crops and four integrated nutrient management (INM) practices was carried out in FRBD with 5 replications. The study revealed that growth and yield of all the vegetable crops grown under coconut were significantly influenced by INM practices. Among the INM practices, pooled analysis of yield data indicated that, S3 treatment (5 tonnes FYM+ 50% NPK + 25% N by vermicompost + 25 % N by composted coir pith (CCP)+ IIHR micronutrient spray) recorded significantly higher yield in okra (9.85 tonnes/ha), baby corn (4.55 tonnes/ha), gherkin (74.87 tonnes/ha) and cucumber (6.51 tonnes/ha) when grown as intercrop in coconut plantation.